Biaya Transaksi dan Benefit Cost pada Integrasi Vertikal Rantai Nilai Agroindustri Kakao Skala Kecil - Zulfiandri Zulfiandri; M. Syamsul Maarif; Aji Hermawan; Hartrisari Hardjomidjojo (School of Business, Bogor Agricultural University (SB-IPB), 2017)
The government has provided incentives of technology to farmer groups engaged in the business of cocoa and chocolate. The incentives are expected to improve the downstream processes of the agricultural commodities. One downstream strategy developed by the government is developing a small capacity of the cocoa industry to undertake the processing of cocoa beans. The government intends to integrate the aquaculture sector (on-farm) with the processing sector (off-farm). This study aimed to analyze the transaction fee on each cocoa agro-industry value chain and analyze the feasibility of cocoa agro-industry vertical integration with benefit-cost ratio analysis in order to obtain the input vertical integration of agro-industry appropriate for cocoa farmer groups in Indonesia. The research showed that transaction costs increased concurrently with the vertical integration between small-scale cocoa value-chains. The vertical integration showed a positive correlation with the feasibility of cocoa agro-industry. If the business is run separately, it is a worthy effort in the early stage and late stage chains (culinary). If the business is integrated between stage 1 and stage 2, the value of BC ratio is still not feasible. The vertical integration stage 1, stage 2 and stage 3 cacao of the agro-industry produced a BC ratio of 1.12, indicating that the business is financially feasible.Keywords: cocoa agroindustry, technology incentives, transaction cost, benefit cost analysis, vertical integration